An Analysis of Exhaust Emissions on a Diesel Engine Operation by Biodiesel - Ilkilic, C. (Taylor & Francis Inc, 2011)
Vegetable oils can be seen as a renewable fuel source for diesel engines. However, their viscosity is higher than that of diesel fuel. The higher viscosity of vegetable oil causes many combustion problems when directly used in diesel engines. In this study, a transesterification method was used to reduce the viscosity of the vegetable oil. Emission characteristics of both biodiesel and diesel fuels were experimentally investigated in an unmodified diesel engine. The test results have shown that the emissions of biodiesel were fairly low as compared to diesel fuel. CO and CO2 emissions of biodiesel were decreased respectively about 56 and 17% in comparison to diesel fuel.
Keywords: biodiesel; CO; CO2; diesel engine; emissions; NOx